First report of the serpentine leafminer Liriomyza huidobrensis (Blanchard) (Diptera: Agromyzidae) and its impacts in Australia. Issue 3 (24th May 2022) - Mulholland, Shannon; Gopurenko, David; Mirrington, Roslyn; Löcker, Birgit; Gillespie, Peter; Rossiter, Louise; Anderson, Chris
Abstract: Serpentine leafminer Liriomyza huidobrensis is a highly polyphagous insect pest that threatens vegetable and ornamental horticultural production globally as a function of feeding and egg laying damage to plants. Although this species has been periodically intercepted at Australia's border, the pest had not been recorded as established on the mainland. A population of L. huidobrensis was identified in the Sydney Basin, New South Wales (NSW), Australia, in late 2020 affecting a variety of vegetable crops. Delimiting surveillance revealed L. huidobrensis to be widespread in the Sydney Basin and present in several regional locations, impacting vegetable, ornamental and weed hosts. This article documents the first report of L. huidobrensis in Australia and the ensuing biosecurity response that was triggered at its detection.